Incidental Findings in Cone Beam Computed Tomography for Dental Implants in 1002 Patients. Issue 8 (23rd February 2021) - Kachlan, Mamdouh O.; Yang, Jie; Balshi, Thomas J.; Wolfinger, Glenn J.; Balshi, Stephen F.
Abstract: Purpose: The purpose of this study is to analyze the frequency and elevate the awareness of the prevalence of nondental pathology in cone beam computed tomography (CBCT) scans taken for implant placement treatment planning and postplacement evaluation. The data from the CBCT should be read by an oral and maxillofacial radiologist for proper diagnosis of dental and nondental pathology and referred to the medical specialist for proper management when necessary. Materials and methods: This retrospective study analyzed 1002 consecutive CBCT scans taken at a single private practice noting the prevalence of nondental pathology in CBCT images for all dental implant procedures. All scans were taken from November 2007 to March 2020. One board certified oral and maxillofacial radiologist systemically read all scans and reported all findings in the maxilla and mandible, condyles and TMJ, paranasal sinuses, nasal fossa, pharyngeal airway, skull base and temporal bone, neck soft tissues, and cervical spine. The incidental findings, variation of normal anatomy, or pathology reported in these structures were categorized based on anatomic location and significance and the incidence was investigated. Results: Pathologies ranged from innocuous sinusitis, to more serious atherosclerotic calcification of the carotid arteries, narrowed airways, and neoplastic lesions. Fifty‐one different findings were noted, of which 36 were pathologies that required referral or follow‐up. Conclusions: Incidental findings can be detected in CBCT scans for dental implants. The clinician must be familiar with the radiographic diagnosis of head and neck pathology, and/or must refer these images to an appropriate specialist for the radiographic interpretation of the full volume.